2009
DOI: 10.1121/1.3272633
|View full text |Cite
|
Sign up to set email alerts
|

Multiple instances of vocal sensorimotor adaptation to frequency-altered feedback within a single experimental session

Abstract: Vocal sensory-motor adaptation is typically studied by introducing a prolonged change in auditory feedback. While it may be preferable to perform multiple blocks of adaptation within a single experiment, it is possible that a carry-over effect from previous blocks of adaptation may affect the results of subsequent blocks. Speakers were asked to vocalize an /a/ sound and match a target note during ten adaptation blocks. Each block represented a unique combination of target note and shift direction. The adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Since the first application of the sensorimotor adaptation paradigm to speech, a number of adaptation studies have supported the original findings for formant perturbations (e.g., Purcell and Munhall, 2006;Villacorta et al, 2007) as well as several additional acoustic manipulations, including shifting the center of spectral energy of fricatives (Shiller et al, 2007(Shiller et al, , 2009 and perturbing fundamental frequency (f o , the acoustic correlate of pitch) during sustained phonation (Jones and Munhall, 2000;Hawco and Jones, 2010). The findings have also been generalized to perturbations of pitch and formant frequencies in Mandarin, a tonal language Munhall, 2002, 2005;Cai et al, 2010), and to sentence-level stimuli with formants of multiple vowels perturbed within an utterance (Lametti et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Since the first application of the sensorimotor adaptation paradigm to speech, a number of adaptation studies have supported the original findings for formant perturbations (e.g., Purcell and Munhall, 2006;Villacorta et al, 2007) as well as several additional acoustic manipulations, including shifting the center of spectral energy of fricatives (Shiller et al, 2007(Shiller et al, , 2009 and perturbing fundamental frequency (f o , the acoustic correlate of pitch) during sustained phonation (Jones and Munhall, 2000;Hawco and Jones, 2010). The findings have also been generalized to perturbations of pitch and formant frequencies in Mandarin, a tonal language Munhall, 2002, 2005;Cai et al, 2010), and to sentence-level stimuli with formants of multiple vowels perturbed within an utterance (Lametti et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…One comparable study that also used a long hold phase (180 trials) without a ramp phase also reported a large proportion of nonresponders (14/30 participants; Scheerer, Tumber, & Jones, 2016), suggesting these factors may influence participant response in adaptive f o studies. However, other prior studies have shown significant adaptation using paradigms without a ramp phase (e.g., Hawco & Jones, 2010) or with comparably long hold phases (e.g., Behroozmand & Sangtian, 2018). Although our data preclude a full analysis of the impact of stimulus type (sustained vowel vs. word) on the likelihood of a following response, our data set included sufficient data from both stimulus types to examine this question in reflexive pitch studies.…”
Section: Comparison Of Compensation Magnitudes Across Tasksmentioning
confidence: 95%
“…Liu, Chen, Jones, Huang, & Liu, 2011) and the earlier Eventide H3000 series (e.g., Burnett et al, 1998;Hain et al, 2000;Jones & Munhall, 2005;Larson et al, 2000;Sivasankar, Bauer, Babu, & Larson, 2005). Another popular hardware used by researchers (e.g., Feng, Xiao, Yan, & Max, 2018;Hawco & Jones, 2010;Jones & Keough, 2008;Mollaei, Shiller, Baum, & Gracco, 2016;Tumber, Scheerer, & Jones, 2014;Zarate & Zatorre, 2008) is the Voice One, made by TC Helicon. The Voice One's pitchshifting algorithm includes formant correction, thereby avoiding issues related to unintended formant frequency changes during pitch-shifting tasks.…”
mentioning
confidence: 99%